PELAKSANAAN WAKAF TANAH YANG TIDAK MEMILIKI AKTA IKRAR WAKAF (AIW) PADA PERUMAHAN MUTIARA KUALU PERMAI - Yolla Indriana; Mardalena Hanifah; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Waqf land in Indonesia has been known and implemented by Muslims since Islamentered Indonesia. Land waqf is one form of waqf object in Indonesia. Waqf has the potentialto advance the economy in Indonesia. This is evidenced by the large amount of waqf land thatshould be developed even more. The problem that occurs is regarding the position of waqfland at Mutiara Kuala Permai Housing. The main problems in this study are: First, how isthe implementation of land waqf that does not have a Waqf Pledge Deed (AIW) at MutiaraKuala Permai Housing Complex? Second, what are the legal consequences of landendowments that do not have a Waqf Pledge Deed (AIW) at Mutiara Kualu Permai HousingComplex?This research is a juridical research or sociological legal research, namely researchconducted directly on location or in the field to obtain data to provide a complete and clearpicture of the problem under study. The population is all parties, namely Mr. Joni Sapriadi,S.E as Nazhir, Mr. Ir. Gustiwan as Head of RT 08/RW 01 Dusun V Kampung Baru, KualuVillage, and Mr. Developer as Mutiara Kualu Permai Housing according to the problemsexamined in this study. Sources of data used primary data sources and secondary data. Datacollection techniques used, interviews and literature review.The results of the research that can be concluded. First, the implementation of waqfland for public facilities that do not have a Waqf Pledge Deed (AIW) at Mutiara Kualu PermaiHousing is known that the existence of land for public facilities from the developer to thecommunity is a form of obligation as a condition that must be met by the developer inobtaining the benefits of the partnership program. subsidized housing from the governmentso that if there is no transfer of land for public facilities, then in essence the housing cannotbe part of the government's subsidized housing program. Based on the status of the landprovided by PT Mutiara Anugerah Mandiri, it is a waqf land. Second, the legal consequenceof a land endowment that does not have a Waqf Pledge Deed (AIW) at Mutiara Kualu PermaiHousing is a violation. In order to avoid sanctions, PT Mutiara Anugrah Mandiri is obligedto complete the Waqf Pledge Deed from the public facility land as soon as possible. Inaddition, for the community, if there is no action from the developer, they can make acomplaint to the Regent through the Kampar Regent through the Kampar District Housingand Settlements Office, Jl. Langgini, Kec. Bangkinang, Kampar District, Riau.Keywords : Waqf – Waqf Land – Waqf Implementation.